MAKNA KESETIAAN DALAM VIDEO KLIP 'GALA BUNGA MATAHARI' KARYA SAL PRIADI - Putri Gifa, Alkausara (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This article examines the representation of loyalty in the music video "Gala Bunga Matahari" by Sal Priadi through the lens of Roland Barthes' semiotic theory. The video was selected due to its strong visual and symbolic elements that portray themes of love and loss, particularly through the central use of the sunflower. The analysis focuses on visual components such as colour, lighting, gestures, and scene composition to interpret the denotative, connotative, and mythological meanings embedded in the visual signs. The findings reveal that loyalty is not always manifested through physical presence, but often lives on through symbols, memories, and emotional gestures. The sunflower functions not merely as a decorative element but emerges as a profound symbol of enduring loyalty, love beyond death, and a bridge between two existential realms. Thus, this music video serves as an emotional narrative and a reflective space that invites viewers to reinterpret experiences of loss and emotional connection. This study highlights how popular visual media can effectively communicate emotional and spiritual values in contemporary culture.